The Dynamics of Qur’anic Text and Translation in Banjarese Ulema’s Works - Wardatun Nadhiroh; Wardani (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2023)
This research presents a comprehensive exploration of Quranic Studies within the context of South Kalimantan, Indonesia, with a specific focus on Islamic works authored by the Banjarese ulema. Historically, a notable void existed in the Banjar literature concerning the Quran, characterized by a dearth of published materials, thereby leaving a substantial lacuna in the Indonesian Quranic scholarship landscape. Employing a comparative methodology and content analysis, this research elucidates the pivotal role and prominence of Quranic texts and translations within Banjarese literary productions. The findings indicate that while Quranic studies in this region encompass diverse dimensions, the examination of the Quran in Tanah Banjar predominantly serves practical applications rather than delving into exegetical discourse. Furthermore, Quranic texts and translations feature prominently across various genres of Banjarese works, serving as foundational sources for authorial assertions, as points of reference, and as tools for elucidation. This research thus contributes to a nuanced understanding of Quranic scholarship in South Kalimantan and underscores the significance of Quranic literature within the broader Indonesian academic landscape.